Management of the Habituation of Students' Daily Rituals: An Analysis of the Function of Islamic Education Management at the Nurul Qur'an Islamic Boarding School - Aliyul Karror; Kacung Wahyudi (Responsive: Jurnal Manajemen Pendidikan Islam, 2026)
The cultivation of daily rituals in Islamic boarding schools is one of the most fundamental and sustainable strategies in Islamic education. However, studies on how management processes are systematically implemented to oversee this cultivation have not yet received sufficient academic attention. This study aims to analyze the application of Islamic educational management functions, including planning, organizing, actuating, and controlling, in the context of managing daily rituals for students at the Nurul Qur'an Islamic Boarding School. The method used is a descriptive qualitative approach with data collection techniques through in-depth interviews with students and teachers directly involved in the habit-forming process. The results of the study indicate that this boarding school has carried out management functions in a structured manner, although there are still several aspects that require strengthening, particularly in the evaluation and documentation stages of the program. The division of roles among the kyai, ustadz, and senior students has been quite effective in ensuring the continuity of rituals. Additionally, the habit-forming methods applied such as modeling, collective supervision, and a reward-punishment system have proven capable of gradually increasing student compliance. These findings offer practical implications for boarding school administrators in designing more measurable and sustainable habit-forming programs.